PENGUJIAN BREAKDOWN VOLTAGE BAHAN ISOLASI PVC KABEL INSTALASI LISTRIK - Muh Rifai Damogalad Rifai; Jumiati Ilham; Ervan Hasan Harun (Program Vokasi-Universitas Negeri Gorontalo, 2023)
This article is a template for writing in the Journal of Renewable Energy Engineering using MS Word. Papers do not need to be numbered. Reports can be written in Indonesian or English. The number of pages is at most seven sheets in A4-two-column format. The title page must include the specific title, author, affiliation, telephone number, and fax number or e-mail address must be given after the author's name. Write the title using Times New Roman 12pt, author's name 11pt, Bold, All caps. The rest of the paper should be written in 10pt Times New Rowman. Before writing, please adjust the margins of your paper to the margins of this template, namely by looking at the page setup of the template that we have provided. An abstract of around 125-300 words is written at the beginning of the article and must contain objectives, methods, results, and conclusions.